The importance of entrepreneurial learning on the example of the South East European Center for entrepreneurial learning in Croatia - Maleković, Sanja; Tišma, Sanja; Keser, Ivana (The European Journal of Applied Economics, 2016)
The paper focuses on the experience in development of entrepreneurial learning (EL) policy in South and East Europe (SEE), as a result of activities implemented by the South East European Center for Entrepreneurial Learning (SEECEL) in Croatia. It aims to explore whether the EL concept, as promoted and developed by SEECEL, can also contribute to development of an entrepreneurial mindset and behaviour, creative thinking, as well as enhancing the development of individual’s entrepreneurial characteristics regardless of their ambition to start/conduct some business. The authors also seek to explore the relevance of the exchange of experience, effective partnership and cooperation of all involved education and other institutions and actors engaged in policy support for further development of the EL approach in SEE. The authors address different perspectives and understandings of the EL concept, point out to the existence of different schools of thought on EL, and consider the interaction between learning and entrepreneurship, which asks for novel and rigorous theorizing.
Keywords: life-long learning; entrepreneurial learning concept; education and training